Education as Part of Migrant Trajectories: A Sociological Study of Pakistani Hindus in a City. Issue 3 (3rd July 2019) - Bhadra, Aratrika
ABSTRACT: The Pakistani Hindu community inhabiting a camp in the city of New Delhi presents the most recent case of South-to-South migration. Migration into India for this community has been undertaken with an aim to achieve a better life, especially one characterized by better education for their children. Education for the families from this community is associated with progress, improvement, development of intellect, and a means to put an end to the families' endless roaming. However, the visions and aspirations for the future meet with difficulties stemming from the nature of their migration and the absence of any transactional relationship with the Indian state due to their lack of citizenship.